Analysis of Social Determinants and the Utilization of Pediatric Tele-Urgent Care During the COVID-19 Pandemic: Cross-sectional Study - Saif Khairat; Phillip McDaniel; Matthew Jansen; Tia Francis; Barbara Edson; Robert Gianforcaro (JMIR Publications, 2021)
BackgroundTelehealth is increasingly used to provide specialty consultations to infants and children receiving care. However, there is uncertainty if the COVID-19 pandemic has influenced the use of telehealth among vulnerable populations. ObjectiveThis research aims to compare the overall use of tele-urgent care visits for pediatric patients before and after the pandemic, especially among vulnerable populations. MethodsWe conducted a cross-sectional analysis of pediatric tele-urgent care visits at a virtual care center at a southeastern health care center. The main outcome of this study was the use of pediatrics tele-urgent visits across geographical regions with different levels of social disparities and between 2019 and 2020. ResultsOf 584 tele-urgent care visits, 388 (66.4%) visits occurred in 2020 during the pandemic compared to 196 (33.6%) visits in 2019. Among 808 North Carolina zip codes, 181 (22%) consisted of a high concentration of vulnerable populations, where 17.7% (56/317) of the tele-urgent care visits originated from. The majority (215/317, 67.8%) of tele-urgent care visits originated from zip codes with a low concentration of vulnerable populations. There was a significant association between the rate of COVID-19 cases and the concentration level of social factors in a given Zip Code Tabulation Area. ConclusionsThe use of tele-urgent care visits for pediatric care doubled during the COVID-19 pandemic. The majority of the tele-urgent care visits after COVID-19 originated from regions where there is a low presence of vulnerable populations. In addition, our geospatial analysis found that geographic regions with a high concentration of vulnerable populations had a significantly higher rate of COVID-19-confirmed cases and deaths compared to regions with a low concentration of vulnerable populations.